WRITING FOR INTERNATIONAL PUBLICATION: AN INTERVIEW WITH NUGRAHENNY T. ZACHARIAS, HANDOYO P. WIDODO AND WILLY A. RENANDYA - Board of Editors (TEFLIN, 2012)
There is a growing pressure in recent years for people working in institutions of higher learning to get themselves published in peer-reviewed international journals. This is true not only for those working in research-focused universities, but also for those in teaching-intensive universities. For those lacking experience, publishing in international journals can be a daunting task. Some may, in fact, feel that only a select few (e.g., those who hold professorial ranks)can get their work published internationally. Even many believe that writing for an international audience is an impossible task to accomplish. To shed this belief away and to make the idea less daunting, TEFLIN Journal initiates to bring about the experience of Indonesian EFL scholars who are nationally and internationally renowned for their publication and contribution to the field. Starting from this issue an interview will be published every other year with the hope that more and more Indonesian scholars are inspired to publish.This piece is brought together by Flora Debora Floris, one of TEFLIN Journal Editors and also a faculty member of the English Department, Petra Christian University, Surabaya, Indonesia. Three productive TESOL scholars from Indonesia: Nugrahenny T. Zacharias of Satya Wacana Christian University, Handoyo Puji Widodo of Politeknik Negeri Jember (both are still in their mid-thirties) and Willy A Renandya, who currently works at the National Institute of Education, Nanyang Technological University, Singapore, were interviewed to not only showcase their work, but also highlight the joy, the reward, the recognition of having their work accepted and acknowledged by members of the international community, and yes, also the pain of having their work rejected by journal editors. More importantly, the key message being sent through this interview is that there is nothing impossible to achieve. The three scholars being interviewed are very passionate about their works, teaching, learning, writing, and publication. This is not to say that writing and getting published is a smooth-sailing process. But, with a bit of passion and hard work, the writing and publication journey can become a bit less overwhelming and more enjoyable.Their writings and publishing experiences are inspiring. Hopefully, the readers of this journal will be inspired to follow their lead. If they can do it, so can many of us who are embarking on this writing and publishing journey.